Photoperiod Sensitivity and Variability of Agromorphological Traits and Brix Content of Sweet Sorghum Cultivated in Burkina Faso under Two Sowing Dates - N. Sawadogo; J. Tiendrebéogo; G. Naoura; T. L. K. Béré; W. H. Tondé; B. Sawadogo; P. Bationo-Kando (Advances in Agriculture)
Sweet sorghum is mainly cultivated for the sweetness of its stems and the quality of its fodder. Unfortunately, its cultivation is gradually being abandoned in Burkina Faso due to climatic hazards. In a general context of strong variations in the rainfall regime, it is, therefore, important to determine the effect of the sowing period on the expression of agromorphological traits and Brix content. Thus, 29 sweet sorghum accessions were evaluated using 15 quantitative variables in a three-replicate Fisher block design with two sowing dates spaced 25 days apart. The results of the study showed that only stalk length (pr. = 0.519) and internode length (pr. = 0.367) were not significantly influenced by sowing date. Indeed, delayed sowing resulted in an increase in the number of vegetative (+2.44) and useful (+1.3) tillers, as well as Brix (+1.16%). However, a reduction in leaf area (−4.35 cm × 1.43 cm), plant height (−85.69 cm), panicle length (−2.63 cm), and panicle weight (−6.19 g), as well as a reduction in the sowing-to-flowering cycle from 3 to 21 days, was obtained at the second sowing date. Thus, all accessions are sensitive to photoperiod with photoperiodic coefficients varying from 0.19 (GB02) to 0.93 (BSA5). These results could be exploited in the sweet sorghum improvement program.